Effects of oral testosterone undecanoate therapy on bone mineral density and body composition in 322 aging men with symptomatic testosterone deficiency: a 1-year, randomized, placebo-controlled, dose-ranging study. (June 2013) - Bouloux, Pierre M. G.; Legros, Jean-Jacques; Elbers, Jolanda M. H.; Geurts, T. B. Paul; Kaspers, Marion J. G. H.; Meehan, Alan G.; Meuleman, Eric J. H.
Abstract Objective: We investigated the effects of oral testosterone undecanoate (TU) on bone mineral density (BMD), lean body mass (LBM) and body fat mass (BFM) in aging men with symptomatic testosterone deficiency (TD). Methods: Three hundred twenty-two men ≥50 years with TD symptoms and calculated free testosterone <0.26 nmol/L participated in a multicenter, double-blind, placebo-controlled trial. Patients were randomized to placebo, oral TU 80 mg/d, oral TU 160 mg/d, or oral TU 240 mg/d, administered as divided doses with normal meals. BMD of the hip and lumbar spine were evaluated by dual energy X-ray absorptiometry (DEXA), and body composition (LBM and BFM) by whole body DEXA. Results: Oral TU significantly increased BMD at Month 12 at the lumbar spine (240 mg/d), total hip (240 mg/d), and trochanter and intertrochanter (160 and 240 mg/d) compared with placebo. Oral TU significantly increased LBM at Months 6 and 12 for all oral TU groups compared with placebo. BFM significantly decreased at Month 6 (all oral TU groups) and Month 12 (160 mg/d) compared with placebo. The effects on BMD and body composition showed a clear dose response. Conclusions: Treatment with oral TU led to improvement in BMD, LBM and BFM in aging men with symptomatic TD.